2016
DOI: 10.1080/23273798.2016.1253852
|View full text |Cite
|
Sign up to set email alerts
|

The syllable in the light of motor skills and neural oscillations

Abstract: International audienceRecent advances in neuroscience have brought a great focus on how the auditory cortex tracks speech at certain time scales corresponding to pre-lexical speech units in order to achieve comprehension. In particular, it has been claimed that it is the syllabic rhythm to which slow neural oscillations in the auditory cortex entrain in order to chunk the speech stream into smaller informational units. However, the terms “syllable” and “rhythm” have been treated quite loosely in the current li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…These phrases had distinct pauses (see Fig 1 for an example sentence) that determined the rhythm of the sentence (also visible in the frequency spectrum S3A Fig ). The syllable rate is generally difficult to assess [ 18 , 79 ]. Here, we chose to count the actually produced syllables for each sentence.…”
Section: Methodsmentioning
confidence: 99%
“…These phrases had distinct pauses (see Fig 1 for an example sentence) that determined the rhythm of the sentence (also visible in the frequency spectrum S3A Fig ). The syllable rate is generally difficult to assess [ 18 , 79 ]. Here, we chose to count the actually produced syllables for each sentence.…”
Section: Methodsmentioning
confidence: 99%
“…The mngu0 1 contains one male English speaker producing over 1,000 utterances, amongst which 594 in the duration range of [2,8] sec were chosen for the present study. The 2sec cutoff allowed at least one cycle of the lowest δ frequency (0.5 Hz) to be included; the 8-sec cutoff excluded sentences with medial pauses.…”
Section: The Corporamentioning
confidence: 99%
“…Rhythmic frames play a vital role in the neurological processing of speech: the recurring oscillations in the ENV facilitate the brain to parse the incoming speech signal for comprehension. It has been demonstrated that the δoscillation (0.5-3 Hz, corresponding to stress/foot rates) and θ-oscillation (3-9 Hz, corresponding to syllable rates) in the auditory cortex entrain to the speech ENV at these modulation rates [6][7][8][9] . These slow neuronal oscillations formulated a temporal window structure whereby the auditory cortex tracks the speech signal at the foot and syllable rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic targets are more accurately detected when they occur within a chunking pattern, especially when the chunking rate is within the frequency range of neuronal delta. Strauß and Schwartz (2017) focus on syllabic speech processing, and challenge the traditional view on syllabic rhythms, which in their view are not clearly defined in terms of acoustic of phonetic features. They suggest that the emergence of syllables as sub-units of speech is constrained by nested cortical oscillations, and reflects the interplay of acoustic-phonetic and motor representations.…”
mentioning
confidence: 99%